Adaptive Partnership between SKB Randong and Ruteng Class II B Prison in Integrating Nonformal Education Programs - Lima, Stofiani Susana; Makleat, Nirwaning; Acan, Herminsia Jesika Pax (Journal of English Language and Education, 2025)
This study aims to analyze the adaptive partnership model between SKB Randong and Ruteng Class II B Prison in implementing nonformal education programs. Employing a qualitative case study design the research explores the mechanisms of planning, implementation, and evaluation encompassing four key activities such as Yoga, Communication Psychology, Barbershop, and Make-up Training. Data were collected through document analysis, participant observation, and in-depth interviews, analyzed using Miles and Huberman’s interactive model. Findings indicate that the adaptive partnership is structured around three main pillars. The pillars are collaborative coordination, implementation flexibility and reflective evaluation. Adaptiveness ensures program sustainability by allowing both institutions to adjust policies and resources in response to contextual dynamics. The integration of psychoeducational and vocational programs enhances emotional well-being, practical competence and a more humanistic institutional image. Theoretically, the study posits adaptive partnership as a mechanism for diffusing social innovation in nonformal education, offering a replicable model of cross-institutional collaboration applicable to other correctional settings.